(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2026)
Concerns regarding body image tend to rise among college students. Individuals with a negative body image will do anything to attain their ideal weight, which can lead to changes in nutritional knowledge, variety in consumption, eating habits, and nutritional status. This study aimed to examine the relationship between body image, nutritional knowledge, food consumption (variety of food consumption and eating habits), and the nutritional status of PKU IPB University students. A cross-sectional design was utilized for this research. The study was conducted from May to October 2025. The findings from Mann-Whitney difference test showed that there was a significant difference in body image scores (Z=-2.285; p=0,022) according to the subject’s region of origin. Besides that, the findings from Spearman Rank correlation analysis revealed that there was a significant positive relationship between body image and restrained eating (r=0,713; p=0,001), as well as nutritional status of the subjects (r=0,556; p=0,001).